The Mesentery in Robot-Assisted Total Mesorectal Excision - Crolla, Rogier M.P.H.; Coffey, J. Calvin; Consten, Esther J. C. (Clinics in Colon and Rectal Surgery, 2022)
In recent decades, surgery for rectal cancer has evolved from an operation normally performed under poor vision with a lot of blood loss, relatively high morbidity, and mortality to a safer operation. Currently, minimally invasive rectal procedures are performed with limited blood loss, reduced morbidity, and minimal mortality. The main cause is better knowledge of anatomy and adhering to the principle of operating along embryological planes. Surgery has become surgery of compartments, more so than that of organs. So, rectal cancer surgery has evolved to mesorectal cancer surgery as propagated by Heald and others. The focus on the mesentery of the rectum has led to renewed attention to the anatomy of the fascia surrounding the rectum. Better magnification during laparoscopy and improved optimal three-dimensional (3D) vision during robot-assisted surgery have contributed to the refinement of total mesorectal excision (TME). In this chapter, we describe how to perform a robot-assisted TME with particular attention to the mesentery. Specific points of focus and problem solving are discussed.
Keywords: robot-assisted total mesorectal excision; surgical technique; mesentery